The Development of Empty Chair Techniques Module for Teachers to Improve Students Self- Dialogue - Nurbaity Nurbaity; Fitri Yana Wanti; Siti Rahmah; Windi Sushanti (Proceedings of AICS - Social Sciences, 2018)
The ability to communicate with oneself is important to help the thinking process. This study aims to develop the media in the form of an empty chair technique module to improve self-dialogue that is suitable for use both independently by teachers and as a medium in counselling guidance services in schools. The research approach used a research and development procedure. Subjects in this study were experts of conceptual and media on the stages of product validation, as well as guidance and counselling teachers as potential users of products at the evaluation stage. The data collected in the form of quantitative and qualitative data with questionnaire and interview as data collection tool. The validation of the product with the conceptual and the media expert leads to the conclusion that the module is in sufficient category and decent to be used after improvement. Experts’ suggestions had been used for module improvements. Teachers of Guidance and Counselling generally rate that the module is very good and also demand for some refinement.Keywords:module development, Empty Chair Technique, self-dialogue.